GROWTH AND SURVIVAL RATE OF DOMESTICATED JIELABU FISH (Betta dennisyongi Tan, 2013) REARED WITH DIFFERENT STOCKING DENSITIES - Saputra, Fazril; Zulfadhli, Zulfadhli; Nasution, Muhammad Arif; Syarif, Ahmad Fahrul; Maftuch, Maftuch; Abdan, Mu'amar; Utami, Diah Ayu Satyari; Sofian, Sofian (Politeknik Kelautan dan Perikanan Jembrana, 2025)
Betta dennisyongi, locally known as Jielabu fish, is an endemic ornamental species originating from southwest Nanggroe Aceh Darussalam, Indonesia. The fish currently faces increasing exploitation and habitat degradation which raise conservation concerns and emphasize the need for domestication efforts. This study aimed to determine an appropriate stocking density for the early culture of B. dennisyongi. The research was conducted from October to December 2023 using a completely randomized design with four stocking densities (1, 2, 3, and 4 fish L⁻¹) with three replications. Juvenile fish collected from the wild were acclimated and reared for 60 days in 10-L aquaria. Biological parameters measured included survival, specific growth rate, length gain, weight gain, feed conversion ratio, and feed efficiency, while water quality was monitored periodically. Stocking density significantly affected survival rate and growth (p < 0.05) of B. dennisyongi, with the lowest density (1 fish L⁻¹) producing the most favorable performance, while densities of 3–4 fish L⁻¹ resulted in reduced outcomes. Feed conversion ratio and feed efficiency did not differ significantly among treatments (p > 0.05). All measured water quality parameters remained within acceptable ranges for Betta fish culture. Overall, the study indicates that lower stocking densities support better biological responses, and that 1 fish L⁻¹ is the most suitable for cultivation, while 2 fish L⁻¹ may serve as an acceptable alternative for practical application. These findings provide a foundation for developing effective domestication protocols and support conservation-oriented aquaculture of this vulnerable endemic species. Betta dennisyongi, yang dikenal secara lokal sebagai ikan Jielabu, merupakan spesies ikan hias endemik dari wilayah barat daya Nanggroe Aceh Darussalam, Indonesia. Peningkatan pemanfaatan dan degradasi habitatnya telah menimbulkan kekhawatiran dalam kegiatan konservasi dan menekankan perlunya upaya domestikasi. Penelitian ini bertujuan untuk menentukan padat tebar yang sesuai untuk pemeliharaan awal B. dennisyongi. Penelitian dilakukan pada bulan Oktober hingga Desember 2023 menggunakan rancangan acak lengkap dengan empat padat tebar (1, 2, 3, dan 4 ekor L⁻¹) masing-masing dengan tiga ulangan. Benih ikan yang dikumpulkan dari alam diaklimatisasi dan dipelihara selama 60 hari dalam akuarium berkapasitas 10 L. Parameter biologis yang diukur meliputi kelangsungan hidup, laju pertumbuhan spesifik, pertambahan panjang, pertambahan bobot, rasio konversi pakan, dan efisiensi pakan, sedangkan kualitas air dipantau secara berkala. Padat tebar berpengaruh nyata terhadap kelangsungan hidup dan pertumbuhan (p < 0.05) B. dennisyongi, di mana padat tebar terendah (1 ekor L⁻¹) memberikan performa terbaik, sedangkan padat tebar 3–4 ekor L⁻¹ menghasilkan performa yang lebih rendah. Rasio konversi pakan dan efisiensi pakan tidak berbeda nyata antarperlakuan (p > 0.05). Seluruh parameter kualitas air berada dalam kisaran yang sesuai untuk budidaya Betta fish. Secara keseluruhan, penelitian ini menunjukkan bahwa padat tebar rendah mendukung respons biologis yang lebih baik, dan 1 ekor L⁻¹ merupakan padat tebar yang paling sesuai, sementara 2 ekor L⁻¹ masih dapat diaplikasikan. Temuan ini menjadi dasar bagi pengembangan protokol domestikasi yang efektif dan mendukung budidaya yang berorientasi pada konservasi bagi spesies endemik rentan ini.